An Advanced Dictionary? Similarities and Differences between Duramazwi ReChiShona and Duramazwi Guru ReChiShona - Chabata, Emmanuel (Lexikos, 2002)
Abstract: In this article a comparative analysis of Duramazwi ReChiShona (DRC) and Duramazwi Guru ReChiShona (DGC) is made. Both DRC and DGC are monolingual Shona dictionaries compiled by a team of researchers under the African Languages Lexical (ALLEX) Project, now the African Languages Research Institute (ALRI). During the compilation process, DRC was known as the General Shona Dictionary and DGC as the Advanced Shona Dictionary. A simple analysis of these titles shows that the dictionaries are similar in some ways and also different in others. The writer tries to show the ways in which DGC is regarded as a more advanced dictionary when compared to DRC. Although the argument of the article is mainly built on those differences which make DGC the more advanced, attention is also paid to the similarities between the dictionaries.Keywords: ALLEX PROJECT, ALRI, DURAMAZWI RECHISHONA, DURAMAZWI GURU RECHISHONA, DICTIONARY, SHONA, HEADWORD, SENSE, MONOLINGUAL DICTIONARY, CORPUS, IDIOM, PROVERB, PITHY SAYINGOpsomming: 'n Gevorderde woordeboek? Ooreenkomste en verskille tussen Duramazwi ReChiShona en Duramazwi Guru ReChiShona. In hierdie artikel word 'n vergelykende ontleding van Duramazwi ReChiShona (DRC) en Duramazwi Guru ReChiShona (DGC) gemaak. Sowel die DRC en DGC is eentalige Sjonawoordeboeke, saamgestel deur ?n span navorsers by die African Languages Lexical (ALLEX) Project, tans die African Languages Research Institute (ALRI). Gedurende die samestellingsproses was DRC bekend as die Algemene Sjonawoordeboek en DGC as die Gevorderde Sjonawoordeboek. 'n Eenvoudige ontleding van hierdie titels toon dat die woordeboeke op sommige maniere eenders en op ander ook verskillend is. Die skrywer probeer die maniere aantoon waarop DGC beskou word as 'n meer gevorderde woordeboek wanneer dit met DRC vergelyk word. Alhoewel die argument van die artikel hoofsaaklik gebou is op daardie verskille wat DGC die gevorderdste maak, word ook aandag gegee aan die ooreenkomste tussen die woordeboeke.Sleutelwoorde: ALLEX PROJECT, ALRI, DURAMAZWI RECHISHONA, DURAMAZWI GURU RECHISHONA, WOORDEBOEK, SJONA, TREFWOORD, BETEKENIS, EENTALIGE WOORDEBOEK, KORPUS, IDIOOM, SPREEKWOORD, PITTIGE GESEGDE